Moral Judgment Competence Between Systems and Administration Students - Francia, Victor Hugo Robles (ETHICS IN PROGRESS, 2015)
It is assumed that the university education positively impacts the student’s moral reasoning. The purpose of this research was to examine the Moral judgment competence MJC between systems and management students at a public university in Hidalgo, Mexico. The effectiveness of their curricula and the university years have impact on students’ moral judgment competence. Data was collected through survey exploration with the Moral Judgment Test completed by 272 administration students and 79 systems students of all semesters. The moral judgment competence was evaluated by C index. The C index score was higher for the management than the systems students. The C index score was slightly lower for senior than freshman students. The scholar years did not improve the senior students’ C index, more years of university career were not associated with the senior students’ C index score. Additionally, the results indicated that moral judgment Competence is the same in any gender of the students. Planned moral judgment competence in university curricula is necessary to improve students’ moral reasoning. In this paper, background, theoretical framework, results are discussed.